Pengaruh DPK, NPF terhadap ROA Unit Usaha Syariah - Khairunnisa; Novien Rialdy (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to analyze the influence of DPK, NPF on ROA of Sharia Business Units. The type of research data with secondary data comes from SPS/OJK. There are at least 36 data that can be explained further. The sampling technique is simple random sampling. The result; The R2 value obtained represents the coefficient of determination. This shows that 24.60% of the variation can be explained by the independent variables in this model; Based on the results of the F test, it can be concluded that the independent variable regression model has a simultaneous effect on the resilience variable so that independent variable regression model can predict the dependent variable; Judging from the results of the t test, this research NPF has an effect and is not significant on the ROA variable. This research aims to analyze the influence of DPK, NPF on ROA of Sharia Business Units. The type of research data with secondary data comes from SPS/OJK. There are at least 36 data that can be explained further. The sampling technique is simple random sampling. The result; The R2 value obtained represents the coefficient of determination. This shows that 24.60% of the variation can be explained by the independent variables in this model; Based on the results of the F test, it can be concluded that the independent variable regression model has a simultaneous effect on the resilience variable so that independent variable regression model can predict the dependent variable; Judging from the results of the t test, this research NPF has an effect and is not significant on the ROA variable.